Blue Rock Extreme Sport Eco Institute for the Western Cape, Sir Lowry's pass - Giliomee, Philip (University of the Free State, 2022)
This dissertation was born through my fascination with the industrial archetype and the growing popularity thereof all over the world. The proposed project handles the growing popularity of extreme sport in South Africa and how a space can be created for those seeking a rush of adrenalin. By addressing the need for a natural environment where individual is allowed to break away from their daily routine, the Blue Rock Extreme Sports Institute assists in providing relief from the growing mental and physical health issues we are faced with. The dissertation handles the opportunities for ecological and architectural development within a quarry, allowing the user to witness the beauty of the historical mining industry and not only see it as wasted space. Through the novel use of the scarred environment and manmade contours, the memory of industrial history will come back to life within the quarry. The levels and slopes left behind within the quarry walls will be used as a way of passage to the waters below through promenades, allowing all users to interact with one another. Researching the different tensile forces used in the mining industry and observing the materials used I was able to develop a conceptual image of what could be possible within the given environment. The impact of the research done could hopefully open people's eyes to the endless architectural opportunities we are faced with, especially in the scars left behind from the distant and recent past.
Dissertation(M.Arch. (Architecture))--University of the Free State, 2022
Keywords: Blue Rock Extreme Sport Eco Institute; Extreme sport in South Africa; Historical mining industry; Mental health; Physical health